Optimization Of Loading And Setting Of Cement Packing Bag On People's Shipping Ship In Maccini Baji Port - Pangkajene Islands Regency - Nurwahidah, Nurwahidah; Susanti, Eva; Nurwahidah, Nurwahidah; Tona, Tasdik; Mubarak, Nur Khairul; Asri, Haerani (Zona Laut Jurnal Inovasi Sains Dan Teknologi Kelautan, 2024)
This research aims to determine the conditions of loading activities on people's cruise ships regarding the cargo of cement packing bags on people's cruises, and the cement packing bag transportation system on people's cruise ships that is in accordance with guidelines by referring to the principles of handling and regulation. In this research, primary and secondary data collection methods were used. Quantitative descriptive research is used to solve problems regarding the conditions of loading activities at ports and public shipping vessels on cement packing bags on public shipping ships and the cement packing bag transportation system on public shipping ships which refers to the principles of cargo handling and management. Based on the results of questionnaire calculations, the conditions of loading activities on people's shipping vessels regarding cement packing bag cargo on people's shipping, depend on human resources, facilities and infrastructure, as well as health and safety, while the results of observations on several activities of the transportation and stopping system on people's shipping vessels must be taken into account. regarding the stowage plan, there is preparation of the loading space/cleaning of holds in the cement bag loading rack, which is not properly coordinated by the officer in charge/officer, the stability of the ship needs to be considered, the condition and location of the loading and unloading equipment, the volume of the loading space and the carrying capacity of the ship, Destination port of cargo, quantity, weight, type and nature of cargo in each hold. The author made observations on 6 ships.